Amniotic fluid embolism: report of a case. - Lindo, Misael (2015)
A case of intrapartum amniotic fluid embolism is presented in a multigesta 40, who had vaginal delivery of healthy child and later died, despite therapeutic measures put in place. A review of current knowledge on this complication is maternal.